Detail in contemporary lighting design - Entwistle, Jill. (London : Laurence King, 2012)
Lighting is a key feature of almost all interiors but it is often treated in a rather superficial manner in most books. It is, however, a complex, fast-moving field where the technology is always changing. For large schemes, a professional lighting designer is usually employed, but for smaller projects it will often fall to the architect or interior designer to specify the lighting. In either case, it is crucial that the architect or interior designer understands what lighting is available, how it can be used and controlled and how it can be fitted. This book features 40 recent international projects. Each project features detailed plans, diagrams, sketches and CAD visuals to demonstrate the lighting techniques involved. This is accompanied by an explanatory text (how the lighting fulfilled the brief, how the lighting concept was arrived at, why particular light fittings/lamps were specified and so on). A bonus CD includes technical drawings from the book.
boek